Therapy's shadow: a short history of the study of resistance to cancer chemotherapy - Peter eKeating; Alberto eCambrosio; Nicole eNelson; Andrei eMogoutov; Jean-Philippe eCointet; Jean-Philippe eCointet (Frontiers Media S.A., 2013)
This article traces the history of research on resistance to drug therapy in oncology usingscientometric techniques and qualitative analysis. Using co-citation analysis, we generatemaps to visualize subdomains in resistance research in two time periods, 1975-1990 and1995-2010. These maps reveal two historical trends in resistance research: first, a shift infocus from generic mechanisms of resistance to chemotherapy to a focus on resistance totargeted therapies and molecular mechanisms of oncogenesis; and second, a movementaway from an almost exclusive reliance on animal and cell models and towards thegeneration of knowledge about resistance through clinical trial work. A close reading ofhighly cited articles within each subdomain cluster reveals specific points of transitionfrom one regime to the other, in particular the failure of several promising theories ofresistance to be translated into clinical insights and the emergence of interest in resistanceto a new generation of targeted agents such as imatinib and trastuzumab. We argue thatthe study of resistance in the oncology field has thus become more integrated withresearch into cancer therapy-rather than constituting it as a separate domain of study, asit has done in the past, contemporary research treats resistance as the flip side totreatment, as therapy's shadow.